Burnishing of AM materials to obtain high performance part surfaces - Michela Sanguedolce; Giovanna Rotella; Maria Rosaria Saffioti; Luigino Filice (Journal of Industrial Engineering and Management (JIEM), 2022)
Purpose: This paper aims to provide a flexible solution to include additive manufacturing into a process chain complying with Industry 4.0 pillars, overcoming major drawbacks in terms of reliability and experimental effort. Design/methodology/approach: The study is based on the combination of real experimental activities and simulated ones. Findings: The main findings of this work consist into validation of the proposed process chain, which proves to be effective in terms of process flexibility (additive manufacturing, burnishing and process simulation acting synergistically), cost and time reduction and final output quality, encouraging customer involvement towards customization. Originality/value: This paper contributes to current research on the application of burnishing process, an easy to implement and environmentally friendly post-processing method to improve the performance of AM products, by providing a unique perspective integrating a reliable simulation model. Other researchers can employ these outcomes towards manufacturing of the future.
Keywords: 650; additive manufacturing; burnishing; simulation; smart manufacturing; sustainability